If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 12 + 4y = 0 Reorder the terms: 12 + X + 4y = 0 Solving 12 + X + 4y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + X + -12 + 4y = 0 + -12 Reorder the terms: 12 + -12 + X + 4y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + X + 4y = 0 + -12 X + 4y = 0 + -12 Combine like terms: 0 + -12 = -12 X + 4y = -12 Add '-4y' to each side of the equation. X + 4y + -4y = -12 + -4y Combine like terms: 4y + -4y = 0 X + 0 = -12 + -4y X = -12 + -4y Simplifying X = -12 + -4y
| 1/2e^3x=20 | | -10(8x-6)=140 | | 2(3x+3)=11 | | 8x+40y+12x= | | 12=k(18) | | 4x-50=-2x+10 | | 62=7x-3(5x+6) | | 37+b=427 | | 16=6+2m | | 130=x+137 | | 5(-3.4k+-7)+(3k+21)= | | X+127=x+67 | | 1.25+.25x=8.00 | | X+27=x+67 | | 94/1000 | | -3k+5k-4+4k= | | 15x=11x-2 | | 116=18x+8 | | 16=3x+5x | | 1x-2-2.1(x+2)=3(x+1.5) | | 9s=62 | | -7(y+1)+2y=8 | | f-66=242 | | 22y=33y | | 723144=0 | | M-3-2m=-3 | | 1+3r-2r=3 | | z=5x+6b-3x-2x | | 1.7a+0.3a=45 | | -19+x=20-42+10 | | 15-3z=-4.5 | | (M+2)x+(m^2-1)y+m^2+M+1=0 |